The ecology of immune state in a wild mammal, Mus musculus domesticus - Abolins, Stephen; Lazarou, Luke; Weldon, Laura; Hughes, Louise; King, Elizabeth C.; Drescher, Paul; Pocock, Michael J. O.; Hafalla, Julius C. R.; Riley, Eleanor M.; Viney, Mark (PLOS Biology, 2018)
Author summary The immune state of wild animals—and the factors that affect this—is largely unknown. Knowing this is important in understanding how infection and disease affects wild animals, and the biology of their pathogens. The paucity of knowledge about wild animals' immune state is in stark contrast to our exquisitely detailed understanding of the immunobiology of laboratory animals. Here, we have investigated the immune ecology of wild house mice—the same species as the laboratory mouse—characterising their adaptive humoral, adaptive cellular, and innate immune state. Firstly, we investigated how immune variation is structured among mouse populations, finding that there can be extensive immune discordance among neighbouring populations. Secondly, we identified the principal factors that underlie the immunological differences among mice, showing that body condition promotes and age constrains individuals’ immune state. By applying a multifactorial analysis to an immune system-wide analysis, our results bring a new and unified understanding of the immunobiology of a wild mammal.